The Impact of Team Conflict, Leadership and Job Demands on Employees Work Stress: Empirical Evidence from Public Organization - Ahmad, Rohana; Mohamed, Ahmad Martadha Mohamed; Wan Abdul Majid, Wan Naqiyah; Abdul Ghani, Latifah; Damin, Zahrul Akmal (IIETA, 2023)
According to the Congress of Unions of Employees in the Public and Civil Service of Malaysia (CUEPACS), nearly 500,000 Malaysian civil servants have been identified as experiencing work stress. By investigating the effects of work stress on civil servants in Malaysia's federal agencies, the relationship between leadership (LS), team conflict (TC), and work stress (WS) in the Malaysian public sector was examined and the mediating effect of job demands (JD) was tested. The sample comprised 626 respondents who worked in Putrajaya, Kuala Lumpur. Data were collected through survey method and quantitative analysis were done employing the structural equation modeling (SEM) to analyze direct and indirect effect. According to the findings, there was a significant positive impact of TC on WS, TC on JD, and LS on JD. Contrarily, the impact of LS on WS was not significant. The JD constructs was identified as mediator of the aforementioned relationships. The practical implications suggested that organizations should place greater emphasis on cultivating a learning culture to successfully adapt and respond to novel external challenges. Leaders could reduce WS by being honest and empathetic towards the employees and granting them the flexibility to spend precious time with their loved ones. In addition, supervisors and managers should use more transformational approaches in their interactions with subordinates. Team members could stay in touch for social support. The findings extended previous research and strengthened the antecedents of WS, namely LS, TC, and JD, in public organization.